2017
DOI: 10.1080/13685538.2016.1271782
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy for prostate cancer increases the risk of Alzheimer’s disease: a nationwide 4-year longitudinal cohort study

Abstract: The present results suggest that ADT use is associated with an increased risk of developing AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Alzheimer’s disease (AD), the fifth leading cause of death in adults over 65 years of age in the United States, is one of the most prevalent neurodegenerative disorders worldwide [ 1 ]. In the United States, an estimated 5.2 million individuals over 65 years of age had AD in 2012 [ 2 ], and the number of people who develop AD is expected to increase by almost triple, to 13.5 million by 2050 [ 3 , 4 ]. AD and cancer are increasingly prevalent with advancing age, and the probability of the co-occurrence of both AD and cancer in the same patient also rises with increasing age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD), the fifth leading cause of death in adults over 65 years of age in the United States, is one of the most prevalent neurodegenerative disorders worldwide [ 1 ]. In the United States, an estimated 5.2 million individuals over 65 years of age had AD in 2012 [ 2 ], and the number of people who develop AD is expected to increase by almost triple, to 13.5 million by 2050 [ 3 , 4 ]. AD and cancer are increasingly prevalent with advancing age, and the probability of the co-occurrence of both AD and cancer in the same patient also rises with increasing age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only three clinical studies have investigated this issue [ 16 , 19 , 20 ] and they were all observational studies. Discrepancy in the incidence of AD (and associated HRs) has been reported in the literature regarding subsequent dementia and AD following ADT for PCa [ 17 , 18 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that lag time was a significant moderator of crude HR in our study, which implies that the lag period selected could affect the HR. Khosrow-Khavar and others [ 19 21 ] set specific lag times. In the case of Khosrow-Khavar et al [ 19 ], a fixed lag period of a year was set and the implementation of time-dependent exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 However, there is increasing evidence that hormonal therapy, which is included more often than not in breast cancer treatment (with or without chemotherapy), also has important effects on brain functioning. 13-17 While the literature on the long-term cognitive effects of hormonal therapy is quite sparse compared to that of chemotherapy, the studies that have investigated this question have reported a negative influence of hormonal therapy on cognition in breast cancer patients. 18-20 It has been shown that hormonal therapy can lead to organizational, activational, neurotropic, and neuroprotective deficits in breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%